2014
DOI: 10.7314/apjcp.2014.15.3.1459
|View full text |Cite
|
Sign up to set email alerts
|

Difference in the Incidences of the Most Prevalent Urologic Cancers from 2003 to 2009 in Iran

Abstract: Background: Urological cancers represent a major public problem associated with high mortality and morbidity. The pattern of these cancers varies markedly according to era, region and ethnic groups, but increasing incidence trends overall makes focused epidemiological studies important. The aim of the present study was to assess the incidence of most prevalent urological cancers in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 35 publications
2
15
0
2
Order By: Relevance
“…This difference might more be due to smoking prevalence and exposure to occupational hazards among men (Ahmadi et al, 2012) The mean age of prostate cancer in our study was 68 and it had no significant changes during this study. The results are in accordance with previous reports from Iran Asian Pacific Journal of Cancer Prevention, Vol 15, 2014 10197 DOI:http://dx.doi.org/10.7314/APJCP.2014.15.23.10193 Demographic Survey of 10 Common Cancers in North Eastern Iran (Basiri et al, 2014, Zahir et al, 2014 Conclusion: our data resulted in better understanding of the epidemiology of various malignancies in the north east of Iran, for example, breast cancer tends to be found in younger patients. The reasons for this earlier age at onset require further investigation through environmental observation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This difference might more be due to smoking prevalence and exposure to occupational hazards among men (Ahmadi et al, 2012) The mean age of prostate cancer in our study was 68 and it had no significant changes during this study. The results are in accordance with previous reports from Iran Asian Pacific Journal of Cancer Prevention, Vol 15, 2014 10197 DOI:http://dx.doi.org/10.7314/APJCP.2014.15.23.10193 Demographic Survey of 10 Common Cancers in North Eastern Iran (Basiri et al, 2014, Zahir et al, 2014 Conclusion: our data resulted in better understanding of the epidemiology of various malignancies in the north east of Iran, for example, breast cancer tends to be found in younger patients. The reasons for this earlier age at onset require further investigation through environmental observation.…”
Section: Discussionsupporting
confidence: 91%
“…In this study we found it as number 8th among most common cancers and also the frequency of bladder cancer was increased during the intervals of our study. This pattern of increase in the incidence could be found in Iranian men by reviewing the reports from past years (Yavari et al, 2009), some reason could be due to risk factors such as cigarette smoking, opium consumption, history of excessive analgesic use and hair dye usage (Basiri et al, 2014). Mean age of bladder cancer worldwide is above 70 years (median73) and the incidence increases with age (Karbakhsh et al, 2013).…”
Section: Discussionmentioning
confidence: 85%
“…Within the Middle Eastern region, Iranian workers have also reported higher incidence and increasing trend of CaP in their country (Talaiezadeh et al, 2013;Basiri et al, 2014). In the Jordan cancer registry study, CaP was one of the major cancer site (Ismail et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…27,28 Los estudios de Abbas B y col. y Masoompour y col. realizados en Irán encontraron hallazgos similares en la distribución por sexos; sin embargo, Abbas B y col. encontraron además un aumento de la incidencia en el tiempo de 8,3/100.000 en hombres y 2,1/100.000 en mujeres para 2003, y 12,5/100.000 en hombres y 3,3/100.000 en mujeres para 2009. 29,30 Finalmente, Mufid D y col. en Libia, fuera de evaluar incidencia, observaron mortalidad encontrando una tasa de 4,3/100.000 en hombres y 0,9/100.000 en mujeres. 31…”
Section: áFrica Y Oriente Mediounclassified